Imunofluorescencná identifikácia limbálnych kmenových buniek v kultúre donorskej rohovky - Kozák, I; Rosocha, J; Hrbková, H; Juhás, T (Ceska a slovenska oftalmologie, 2003)
The purpose of this study was to identify limbal stem cells in the culture of human donor cornea. After standard cultivation procedure we used monoclonal antibody against alpha-enolase for identification of stem cells. This antibody serves as a probe for the identification of biochemical marker of stem cells. Using immunofluorescent microscopy we identified in specimens alpha-enolase positive cells which in vitro but not in situ showed also some morphologic differences from other cellular elements of the culture.
Keywords: Phosphopyruvate Hydratase; Fluorescent Antibody Technique; Limbus Corneae; Stem Cells; kultivované buňky; Cells, Cultured; transplantace rohovky; monoklonální protilátky; Antibodies, Monoclonal; Humans; lidé; fosfopyruváthydratasa; kmenové buňky; limbus corneae; Corneal Transplantation; fluorescenční protilátková technika